Magnetocaloric properties of low-cost Fe and Sn substituted MnNiSi-based alloys exhibiting a magnetostructural transition near room temperature - Deepak, Kamble (2020)
The magnetocaloric properties of rare-earth free Mn0.45Fe0.55NiSi1-ySny (y=0.12, 0.14, 0.16, and 0.18) alloys were studied. The raw material cost is significantly lower than the counterpart alloys containing Ge or Ga. Sn substitution reduced the Curie temperature (Tc) from 343 K (for y=0.12) to 248 K (for y=0.18), offering a wide range of working temperatures near room temperature. The alloys exhibited a training effect. The first-order transition weakened as the Sn content increased from 0.12 to 0.18. Interestingly, magnetostructural transformation was observed near room temperature for y=0.14, with a maximum entropy change (Δ Smax) of 8.64 Jkg-1K-1 for a field change of 5 T. Hence, Mn0.45Fe0.55NiSi1-ySny alloys are promising candidates for low cost, near room temperature, magnetocaloric applications.